A review on fatty acid desaturases of psycrophilic bacteria and unsaturated fatty acids - Garba, Lawal; Mohamad Ali, Mohd Shukuri; Oslan, Siti Nurbaya; Raja Abdul Rahman, Raja Noor Zaliha (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
Fatty acid desaturase enzymes function in the introduction of a double bond into fatty acyl chains to produce unsaturated fatty acids. Unsaturated fatty acids play significant role in maintaining the right structure and functioning of biological membranes of all organisms. Psychrophilic bacteria survive low temperatures with 15 °C and 20 °C as the optima and maxima respectively. Under these conditions, the bacteria modulate their membrane fluidity by means of synthesizing more unsaturated fatty acids using desaturase enzymes. Consequently, transport of nutrients and metabolic wastes in and out of the cell are properly regulated. Moreover, unsaturated fatty acids are directly involved in cellular processes like membrane fusion and fission, signalling and energy storage. Furthermore, unsaturated fatty acids have proven antitumor effect, protection against cardiac diseases, antibacterial and anti-inflammatory properties. This review surveys the general aspects of fatty acid desautrases, desaturases of psychrophilic bacteria, unsaturated fatty acids and their roles.